A Critical Study of the Role and Relevance of the Hadith Center in Global and Contemporary Contexts - Mahatir Fathoni; Dedo Diawansyah; Dadah Dadah; Rizzaldy Satria Wiwaha (al-Afkar, Journal For Islamic Studies, 2026)
The digitisation of hadith has changed the landscape of Islamic studies globally, providing quick, broad, and interactive access to classical hadith sources. This study examines the strategic role of digital hadith maktabah in strengthening contemporary Islamic propagation, education, and research and evaluates the serious challenges that come with it, such as the spread of false hadith, copyright issues, commercialisation of knowledge, and data manipulation. Through a descriptive-analytical qualitative approach and critical literature review, this study shows that although the hadith maktabah offers easy access and efficiency, it still requires ethical standards, academic verification, and interdisciplinary collaboration to maintain the authenticity and integrity of Islamic scholarship in the digital era. The findings confirm the importance of integration between modern technology and classical scientific traditions in the responsible and sustainable utilisation of the hadith maktabah.